Assessment of prevalence of dental pulp stones in patients undergoing orthodontic treatment (Orthodontic Journal of Nepal, 2021)
Introduction: Pulp stones are foci of calcification in the dental pulp. During the orthodontic tooth movement, a complex series of tissue reaction occurs. Studies show that the orthodontic force application may cause pulpal changes like pulpal calcifications. Hence; we assessed the prevalence of prevalence of dental pulp stones in patients undergoing orthodontic treatment.Materials and Method: A total of 50 patients who were scheduled to undergo non-extraction orthodontic treatment were included. Pre-treatment and Post-treatment radiographs were taken in all the patients. Evaluation of the permanent molars (maxillary and mandibular) was done, both pre-treatment and post-treatment. Interpretation of the radiographs was done by skilled and experienced oral radiologists. Diagnosis of pulp stones was done when definite radiopaque bodies as dental pulp stones were noted as present or absent. All the results were recorded in Microsoft excel sheet.Results: At pre-treatment time, prevalence of pulp stones was found to be 26 percent, while at post-treatment time, the overall prevalence of pulp stones was found to be 48 percent. Significant results were obtained while comparing the pretreatment and post-treatment prevalence of pulp stones.Conclusion: Formation of pulp stones might be triggered under the effect of orthodontic trea